Analysis of Health Utilization Services in Worship Place - M L I Ansori1 , Aryo Dwipo Kusumo2, D.Y Tandy1 , Windhu Purnomo3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background. Good health services will greatly affect health improvement and treatment. One of the health service facilities is the mosque health service. The number of visits to mosque health services from 2016- 2018 decreased by 49.1%. Purpose. This study aims to determine the factors that influence the worshipers of the mosque in the utilization of mosque health services in Surabaya Ittihad mosque. Method. This study design used descriptive method with cross sectional research design. Population and samples were the entire worshipers of the Ittihad mosque. The number of samples 123 respondents with sampling techniques conducted by means of purposive sampling. Data was collected by interview using a questionnaire. Data analysis used Chi Square test. Results. This study shows that the sex of mosque worshipers (p = 0,604), age (p = 0,617), education (p = 0,690), occupation (p = 0,243), knowledge about mosque health services (p = 0,999), mosque health service Tariff (p = 0.645), and access to information (p = <0.001). Conclusion. It can be concluded that the factors that influence the utilization of mosque health services are access to information provided by the mosque and mosque health services.